2008
DOI: 10.3797/scipharm.0810-11
|View full text |Cite
|
Sign up to set email alerts
|

Activities of the Antipsychotic Drugs Haloperidol and Risperidone on Behavioural Effects Induced by Ketamine in Mice

Abstract: This study presents the actions of risperidone (Risp) and haloperidol (Hal) on the behavioral effects elicited by ketamine (Ket) on open-field (OF), rota rod (RR) and tail suspension (TS) tests in mice. Male Swiss albino mice (25-30g) were used. Antipsychotics were administered alone (Risp: 0.1 or 0.2 mg/kg, ip; Hal: 0.1 and 0.2 mg/kg, ip) or thirty minutes before Ket (10 mg/Kg, ip). Ket increased (Ket: 63.3 ± 4.2) the locomotor activity compared to control, while neuroleptics decreased it (25.5 ± 4.2). Pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…The rota rod test, as a model for forced motor coordination (an index of extrapyramidal symptom) was carried as described by Arruda et al [33]. The apparatus (Ugo basile, Model57625) consisted of a horizontal metal rod coated with rubber (3 cm diameter) attached to a speed motor.…”
Section: Effect Of Morin On Motor Coordinationmentioning
confidence: 99%
“…The rota rod test, as a model for forced motor coordination (an index of extrapyramidal symptom) was carried as described by Arruda et al [33]. The apparatus (Ugo basile, Model57625) consisted of a horizontal metal rod coated with rubber (3 cm diameter) attached to a speed motor.…”
Section: Effect Of Morin On Motor Coordinationmentioning
confidence: 99%
“…Haloperidol reduces cortical activation and, consequently, the recruitment and rate modulation of motor units in the spinal cord (Parr-Brownlie, Hyland, 2005). Previous work in our laboratory showed that it was able to block ketamine-induced hyperlocomotion in mice (Arruda et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Ketamine is a NMDA antagonist that, in acute doses, increases locomotor activity in mice (Arruda et al, 2008;Yamamoto et al, 1997). The mechanism by which ketamine produces hyperlocomotion, at least in part, have been attributed to the blockade of NMDA receptors located on inhibitory GABAergic neurons at limbic and subcortical brain regions, disinhibiting glutamatergic transmission in the prefrontal cortex and ventral tegmental area.…”
Section: Discussionmentioning
confidence: 99%
“…It is well described in the literature that repeated administration of KET is used as an animal model to induce behaviour such as schizophrenia‐like . Since the deficits in PPI and hyper locomotion induced by KET are related to positive‐ and negative‐like symptoms of schizophrenia .…”
Section: Discussionmentioning
confidence: 99%
“…It is well described in the literature that repeated administration of KET is used as an animal model to induce behaviour such as schizophrenia-like. [3,[31][32][33] Since the deficits in PPI and hyper locomotion induced by KET are related to positive-and negative-like symptoms of schizophrenia. [31,33,34] We can suggest that Eryt reversed these symptoms induced by KET with results comparable to those obtained with olanzapine, an atypical antipsychotic drug widely used in the psychiatric clinic.…”
Section: Discussionmentioning
confidence: 99%